2000
DOI: 10.4141/s99-097
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of chemical and physical properties of boreal plain soils impacted by pipeline burial

Abstract: Soon, Y. K., Arshad, M. A., Rice, W. A. and Mills, P. 2000. Recovery of chemical and physical properties of boreal plain soils impacted by pipeline burial. Can. J. Soil Sci. 80: [489][490][491][492][493][494][495][496][497]. Pipeline construction on the Canadian boreal plain occurs on woodland and/or agricultural fields, but soil recovery from its impact is not well documented. Therefore, we quantified changes over 3 yr (1992 to 1994) in the chemical properties of two Grey soils and the physical properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 15 publications
2
29
0
Order By: Relevance
“…Soon et al (2000a) concluded that normal crop and soil management practices maintained crop yields on soils disturbed by pipeline installation even though soil biological properties had not fully recovered. Bulk density and water infiltration also improved after 2-3 yr as a result of natural processes and annual cropping (Soon et al 2000b). In the absence of organic amendments, Naeth et al (1987) believed it would take 50 yr to restore half the SOM lost due to gas pipeline installation on Solenetzic native rangeland in southern Alberta.…”
Section: Discussionmentioning
confidence: 99%
“…Soon et al (2000a) concluded that normal crop and soil management practices maintained crop yields on soils disturbed by pipeline installation even though soil biological properties had not fully recovered. Bulk density and water infiltration also improved after 2-3 yr as a result of natural processes and annual cropping (Soon et al 2000b). In the absence of organic amendments, Naeth et al (1987) believed it would take 50 yr to restore half the SOM lost due to gas pipeline installation on Solenetzic native rangeland in southern Alberta.…”
Section: Discussionmentioning
confidence: 99%
“…During construction, ground excavation can reduce land stability and increase soil erosion, especially in mountainous regions (Yu et al 2010). Various studies indicate that soils inside a pipeline corridor have a lower organic matter and a higher pH than undisturbed soils (Soon et al 2000a;Kowaljow and Rostagno 2008). Trenching to install underground pipelines may change the soil profile by mixing different soil horizons (Olson and Doherty 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The soil properties were relatively stable in comparison to the vegetation properties, except in the WAs, which were affected by the soil mixing when the pipeline trench was backfilled (Ivey and McBride 1999;Soon et al 2000). Therefore, the scopes of the effect on soil quality were narrow in both areas.…”
Section: Discussionmentioning
confidence: 94%
“…As mentioned above, soil properties and vegetation are clearly affected by pipeline construction (Soon et al 2000;CoiffaitGombault et al 2012), and both can be important representations of ecosystem degeneration (Pei et al 2008). This has led to a focus on soil and vegetation in the study of the effects of pipeline construction in recent years (Coiffait-Gombault et al 2012;Olson and Doherty 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation